Performance Evaluation of a Recyclable Bottle-Blade Overshot Waterwheel for Low-Head Low-Flow Pico Hydropower Applications - Basar, Mohd Farriz; Zulkarnain, Izzatie Akmal; Sopian, Kamaruzzaman; Adanta, Dendy; Trenado, Carlos (International Journal of Integrated Engineering, 2026)
This study presents the design and performance evaluation of an innovative bottle blade overshot waterwheel specifically developed for pico hydropower generation in low-head and low-flow conditions. The waterwheel incorporates a lightweight, portable structure with turbine blades constructed from recycled plastic bottles, offering a sustainable and cost-effective solution that also facilitates easy maintenance and reduces plastic waste. Experimental testing was conducted using a water test rig equipped with a Prony brake system, operating under water heads of 0.4 meters and 0.5 meters with flow rates of 0.015 m3/s and 0.02 m3/s. System performance was evaluated based on the fundamental principles of mass, momentum, and energy conservation. Two configurations of the waterwheel, using four and eight bottle blades respectively, were tested to assess the influence of blade quantity on energy conversion efficiency. Key performance indicators included rotational speed (n), angular velocity (ω), torque (τ), tangential force (FT), lift force (FL), blade velocity ratio (U divided by v), mechanical power output (Pmech), mechanical efficiency (ηmech), and electrical efficiency (ηelec). Results were analyzed using graphical performance curves and a nomographic method to visualize the effects of operational parameters. The results demonstrate that both the hydraulic head and the number of blades significantly influence performance. The eight-blade configuration operating at a water head of 0.5 meters and a flow rate of 0.02 m3/s exhibited the highest performance, achieving a mechanical power output of 48.58W, a mechanical efficiency of 49.11%, and an electrical efficiency of 24.03%. This condition corresponded to an angular velocity of 19.48 rad/s, a torque of 2.49 Nm, and tangential and lift forces of 11N and 16.25N respectively. In conclusion, the bottle blade overshot waterwheel demonstrates significant potential for decentralized renewable energy generation in remote or resource-constrained areas, offering an environmentally responsible and technically viable solution for pico hydropower applications.